Studies on non-specific Anorexa in cattle - Baby P G (Department of Clinical Medicine, College of Veterinary and Animal Sciences, 1989)
Non – specific anorexia as a peculiar clinical syndrome in cattle was observed for the last one and a half decades in Kerala. Sample survey on the incidence of this syndrome was conducted through the selected veterinary hospitals in the field and of the Kerala Agricultural University. During the period of 1978 – 1982, anorexia syndrome in cattle constituted 10.95 per cent of the total and 32.30 per cent of their digestive disorders. The incidence of the syndrome was also noted high during the months of November to April every year. Ten apparently healthy cattle maintained under identical conditions of feeding and management at the University Livestock Farm, Mannuthy were selected at random and used as the control animals (Group I) for this study. Twenty selected clinical cases of non – specific anorexia presented at the University Hospital, Mannuthy were divided into groups of ten each (Group II and GroupIII) and utilized for these investigations. Course of the disease was followed and samples of rumen liquor and blood were collected and analysed on the first, third and fifth days of their admission in the clinic. Inappetance, mucopurulent nasal discharge, dryness of the muzzle, followed by peeling of its epithelium, constipation or diarrhea, weakness, emaciation and also marked reduction in milk yield in the lactating animals were the clinical manifestations noted in the affected animals. Their rectal temperature was normal, pulse weak and rapid, respiration normal but sometimes labored and visible mucous membranes were pale or became icteric in the later stages of the disease. Rate of rumen motility was reduced and feeble in strength with rumination remaining suspended. Animals of group II were given conventional therapy comprising oral administration of alksline stomachics. Animals of group III were given 25 per cent dextrose solution and vitamin B – complex with liver extract parenterally and stomachics orally on the first, third and fifth days of their admission in the clinic. Rumen liquor of animals of groups II and III was light yellow, olive green or greenish in colour, aromatic / offensive in odour and thick/thin in consistency on the first day of observation. Protozoal motility was poor (+) to vigorous (+++) and sedimentation activity time was prolonged significantly on the first day. The mean pH of the rumen Liquor of these animals was not significantly different from that of the healthy group. Increase in the ammonia nitrogen level and decrease in total volatile fatty acids concentration in the rumen liquor observed on the first day were significant. Blood glucose, total bilirubin, total protein, albumin and albumin/globulin ratio in the serum were changed significantly in animals with non – specific anorexia. Significant changes observed in the above parameters in group II animals were further enhanced on third and fifth days of observation. In group III animals, a decrease in the ammonia nitrogen level and increase in the total volatile fatty acids concentration in the rumen liquor observed on the third and fifth day of admission in the clinic was statistically significant. Blood glucose, albumin – globulin ratio in the serum were also increased significantly in group III animals on fifth day. Following modified line of therapy the animals of group III became normal within three to five days. Clinical improvement was indicated by increased appetite, revival of rumen motility and rumination and also increased milk yield in the lactating animals. Decrease in the ammonia nitrogen level and increase in the total volatile fatty acids concentration in the rumen liquor of group III animals were significant on fifth day of therapy. Increase in blood glucose, albumin, albumin ratio in the serum were also found to be statistically significant on the fifth day. The changes in the blood glucose, total bilirubin, total protein, albumin and albumin – globulin ratio in the serum indicated hepatic insufficiency possibly responsible for the anorexia developed in the diseased animals. The modified line of therapy was found to be superior to conventional therapy for the clinical management of non – specific anorexia in cattle.